Comparing the Feeding of Fungus Myceliated Grain with Other Anticoccidial Control Measures on Oocyst Excretion of Eimeria Challenged Broilers - Willis, W.L.; Isikhuemhen, O.S.; Minor, R.C.; Hurley, S.; Ohimain, E.I. (International Journal of Poultry Science, 2010)
An experiment was conducted to determine if dietary Fungus Myceliated Grain (FMG) as an alternative to other coccidiosis control measures would result in oocyst reduction in the presence of a field strain Eimeria challenge during grow out. A total of 144 broiler chicks were assigned to 8 treatment groups as follows: 1) Control (no coccidiosis protection - no challenge); 2) 5%-FMG (no challenge); 3) Inovocox (IC) (no challenge); 4) Coccivac-B (CB) (no challenge); 5) Control (no coccidiosis protection, challenged); 6) 5% FMG (challenged); 7) Inovocox (IC) (challenged) and 8) Coccivac-B (CB) (challenged). Broilers were challenged with a mixture of E. acervelina, E. maxma and E. tenella at 28 days of age. Fecal oocyst egg count, mortality and whole blood differentials were measured. The Eimeria counts 1 week post challenge were significantly higher for all challenged chickens (trts 5-8) as compared to unchallenged (trts 1-4). Oocyst counts at day 49 of challenged but unprotected chickens (trt 5) was significantly (p>0.05) greater and showed a higher percentage of mortality when compared to challenged treated groups (trt 6-8). Treatment 6 (5% FMG) led to a reduction in fecal oocyst counts and protected against mortality at rates comparable to the vaccine control methods. Additionally, there were comparable increases in macrophages, heterophils and lymphocytes in the 5% FMG and vaccine groups. The results from this study strongly suggest that a diet supplemented with 5% FMG can be used as an alternative to other coccidiosis control methods in reducing Eimeria oocyst numbers during grow out.